The Influence of the Problem Based Learning Model Based on Tri Nga Teachings on Social Sciences Learning Outcomes in Elementary : Pengaruh Model Problem Based Learning Berbasis Ajaran Tri Nga Terhadap Hasil Belajar IPS Di Sekolah Dasar - Indah Pramesti, Riza; Dewi Wulandari; Nita Kusumawardani; Heri Maria Zulfiati (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This research aims to determine the effect of the Problem Based Learning (PBL) learning model on social studies learning outcomes for Class V Elementary School in Gugus Sumberarum, Kapanewon Moyudan, Sleman Regency. This research is pre-experimental research, with a quasi experimental research design. The population in this study consisted of VA and VB classes with 52 students. Sampling used the Simple Random Sampling technique to select the VA class with 20 students as the experimental class and the VB class with 20 students as the control class. The test instrument used is a learning outcomes test. Data is described and analyzed using descriptive statistics and inferential statistics. The results of the research show that the value of learning outcomes before implementing the Problem Based Learning (PBL) learning model based on Tri Nga teachings obtained an average value of 67.6. After implementing the Problem Based Learning (PBL) learning model based on Tri Nga teachings, the average score rose to 85.35. The results of the significance test obtained a Sig value. (2-tailed), namely 0.00 < 0.05, it can be said that there is a significant difference between the control class and the experimental class, so it can be said that H0 is rejected and H1 is accepted. Based on these results, it can be said that there is a positive influence of the application of the Problem Based Learning (PBL) learning model based on Tri Nga teachings on social studies learning outcomes in class V elementary school in Gugus Sumberarum